Proteomic Analysis Reveals Sex-Specific Protein Degradation Targets in the Amygdala During Fear Memory Formation - Farrell, Kayla; Musaus, Madeline; Navabpour, Shaghayegh; Martin, Kiley; Ray, W. Keith; Helm, Richard F.; Jarome, Timothy J. (Frontiers in Molecular Neuroscience, 2021)
Ubiquitin-proteasome mediated protein degradation has been widely implicated in fear memory formation in the amygdala. However, to date, the protein targets of the proteasome remain largely unknown, limiting our understanding of the functional significance for protein degradation in fear memory formation. Additionally, whether similar proteins are targeted by the proteasome between sexes has yet to be explored. Here, we combined a degradation-specific K48 Tandem Ubiquitin Binding Entity (TUBE) with liquid chromatography mass spectrometry (LC/MS) to identify the target substrates of the protein degradation process in the amygdala of male and female rats following contextual fear conditioning. We found that males (43) and females (77) differed in the total number of proteins that had significant changes in K48 polyubiquitin targeting in the amygdala following fear conditioning. Many of the identified proteins (106) had significantly reduced levels in the K48-purified samples 1 hr after fear conditioning, suggesting active degradation of the substrate due to learning. Interestingly, only 3 proteins overlapped between sexes, suggesting that targets of the protein degradation process may be sex-specific. In females, many proteins with altered abundance in the K48-purified samples were involved in vesicle transport or are associated with microtubules. Conversely, in males, proteins involved in the cytoskeleton, ATP synthesis and cell signaling were found to have significantly altered abundance. Only 1 protein had an opposite directional change in abundance between sexes, LENG1, which was significantly enhanced in males while lower in females. This suggests a more rapid degradation of this protein in females during fear memory formation. Interestingly, GFAP, a critical component of astrocyte structure, was a target of K48 polyubiquitination in both males and females, indicating that protein degradation is likely occurring in astrocytes following fear conditioning. Western blot assays revealed reduced levels of these target substrates following fear conditioning in both sexes, confirming that the K48 polyubiquitin was targeting these proteins for degradation. Collectively, this study provides strong evidence that sex differences exist in the protein targets of the degradation process in the amygdala following fear conditioning and critical information regarding how ubiquitin-proteasome mediated protein degradation may contribute to fear memory formation in the brain.